Karakteristik dan Aktivitas Antioksidan Velva Bayam Merah dan Penstabil CMC (Carboxyl Metyl Cellulose) - Vritta Amroini Wahyudi; Winda Cancerina Harsono Putri; Elfi Anis Saati (Universitas Muhammadiyah Malang, 2021)
Red spinach is known as a food stuff for protein, vitamins A, B, and C and contains mineral salts. Red spinach is used as a natural dye because it is thought that red spinach has betacyanin and anthocyanin content that can produce a purpleish red color. Efforts to increase vegetable consumption are carried out by modifying as a velva, a frozen beverage product that are almost the same as low-fat ice cream Velva. The purpose of this study is to know the interaction of the addition of red spinach extract and CMC stabilizing material, to know the influence of red spinach concentration, and to know the influence of differences in cmc concentrations on Velva characteristics. The implementation of the experiment used a Randomized Group Design (RAK) that was factorially arranged consisting of 2 factors. Factor 1 is the concentration of red spinach extract consisting of 3 levels namely 20%, 25%, and 30% while factor 2 is CMC concentration consisting of 3 levels which is 0.5%, 0.75%, and 1%. Observation parameters include vitamin C levels, melting power, viscosity, antioxidants, anthocyanins, and organoleptics that include color, aroma, taste, texture, and fondness. The results showed that red spinach extract had a significant effect on antioxidants with the greatest value in B3 treatment (Spinach Extract 30%) 53.70%; vitamin C with the greatest value in B3 treatment (CMC 1%) 6.3 g/mL, and anthocyanins with the best 3 treatments are B3 at 1.1675 mL/L, while CMC has a significant effect on melting power, viscosity, and vitamin C Velva spinach red. The results showed that red spinach Velva contains a small amount of glycine so that the pigment contained is betacyanin.